Amino acid metabolism in athletes and non-athletes with special reference to amino acid concentrations and protein balance in exercise, training and aging - Pitkänen, H. (Studies in Sport, Physical Education and Health, 2002)
Amino acids are the basic components of proteins, which are essential to maintain and develop muscle, bone, cartilage, skin and blood. As a response to a physical stress amino acids are mobilised from the body`s free amino acid pool, which is located in the plasma and in cellular spaces. The pool represents only 2% of the total amino acids in the body of a 70-kg individual and approximately half of it exists in skeletal muscle. Despite the small size of the pool it has an important daily task in the protein metabolism. The present study was designed firstly to compare serum amino acid responses to different exercise sessions and to a training period with and without leucine (LEU) supplementation. Secondly, muscle protein balance after a strength training session was examined. The third purpose was to create a profile of the serum amino acid concentrations for aging men and women. The results indicated that the concentration of the sum of all serum amino acids decreased following a training period and following a strength exercise session but not after lactic anaerobic running exercise sessions with protein intake of 1.1-1.3 g/kg body weight/day. The amino acid concentration seemed to decrease following a speed and strength training period of five weeks even though increases were seen in testosterone, cortisol and testosterone/cortisol -ratio showing an anabolic state. LEU supplementation seemed to prevent both a training-induced and an exercise-induced decrease in the serum LEU concentration and to decrease the serum concentration of isoleucine and valine. However, the supplementation did not enhance performance. In fasting conditions, a strength exercise session induced different responses in femoral arterious, femoral venous and muscle concentrations of free amino acids. Both protein synthesis and breakdown increased in fasting conditions following a strength exercise session, but there were no changes in the protein net balance, which was catabolic. Furthermore, the results showed that the concentrations of amino acids decreased significantly with aging and the concentrations were greater in men than in women. This study provides evidence that there are changes in amino acid metabolism following exercise sessions and training periods and that LEU supplementation has an effect on these changes. In fasting conditions, protein breakdown is greater than protein synthesis during recovery following resistance exercise. Serum amino acid concentrations decrease with age and men have greater amino acid concentrations than women.